The performance of young football players in terms of their respiratory function, contingent upon their position on the field - Kozhevnikov V.S.; Alabuzhev S.A.; Lazarenko V.G. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to comparative analysis of the key indicators of external respiration in football players across different stages of adolescence. Methods and structure of the study. The function of external respiration was studied in 102 adolescents aged 12-17 years who study at the Zenit-Izhevsk SSHOR Football Center. All athletes were divided into groups according to two criteria: age and playing role. The Spirolab III device was used, designed for the most complete assessment of the function of external respiration. The following spirometric tests were performed. Results and conclusions. All indicators of respiratory function, expressed as a percentage of the expected values, undergo the following transformations: an increase from 12 to 13 years, followed by a decrease, sometimes abruptly, in the 13-15 year range, and then a gradual rise in the values of all indicators up to 16-17 years. This pattern suggests a significant decline in the function of external respiration and, consequently, aerobic abilities during the 13-15 year period. Therefore, it is crucial to recognize not only sensitive but also challenging phases in the development of general endurance. It is imperative to conduct a comprehensive analysis of respiratory function indicators in adolescent athletes to accurately assess their aerobic capabilities and pinpoint the onset and conclusion of each sensitive period for the purposeful enhancement of general and, to some extent, specific endurance.